Can ChatGPT help patients understand radiopharmaceutical extravasations? - Alvarez, Madeleine (Frontiers in Nuclear Medicine, 2024)
A previously published paper in the official journal of the Society of Nuclear Medicine and Molecular Imaging (SNMMI) concluded that the artificial intelligence chatbot ChatGPT may offer an adequate substitute for nuclear medicine staff informational counseling to patients in an investigated setting of 18 F-FDG PET/CT. To ensure consistency with the previous paper, a similar methodology was followed to evaluate ChatGPT's ability to substitute for nuclear medicine staff counseling on radiopharmaceutical extravasations. We asked ChatGPT fifteen questions regarding radiopharmaceutical extravasations. Each question was queried three times. Using the same evaluation criteria as the previously published paper, the ChatGPT responses were evaluated by two nuclear medicine trained physicians and one nuclear medicine physicist for appropriateness and helpfulness. These evaluators found ChatGPT responses to be either highly appropriate or quite appropriate in 100% of questions and very helpful or quite helpful in 93% of questions. The evaluators also rated the inconsistency across the three ChatGPT responses for each question and found irrelevant or minor inconsistencies in 87% of questions and some differences relevant to main content in the other 13% of the questions. One physician evaluated the quality of the references listed by ChatGPT and concluded that ChatGPT used fully validated references. Based on these results we concluded that ChatGPT may be a reliable resource for patients interested in radiopharmaceutical extravasations. However, ChatGPT responses on radiopharmaceutical extravasations differ significantly from SNMMI and nuclear medicine staff positions. As patients increasingly rely on the internet for medical information, these discrepancies need to be addressed.